Desarrollo e implementación de una aplicación web integrada al programa personal Communications Iseries Access orientada a la gestión del sistema comercial (SICO-CNEL) para la automatización de procesos manuales de Coniel Cia. Ltda. - Córdova Dávila, Jhonsson Xavier (2015)
In the research work the company CONIEL CIA.LTDA, it became necessary to optimize the time involved the implementation of administrative processes and improve the quality of service to users, so the idea of ​​developing the theme of thesis entitled "Development and Implementation of an Integrated web Application to Personal Communications program oriented Iseries Access Management Commercial System (Sico-COL) for Process Automation manuals Coniel Cia.Ltda", which allowed to solve the absence an application that helps streamline administrative processes such as finding information on the SICO CNEL EP System, management contract operational activities, reporting, monitoring work progress, photo management by activity. The project was developed using development methodology Uwe software that focuses on developing models to help understand and analyze the business logic, user requirements, navigability and presentation system and finally the aforementioned methodology he managed the implementation of the application on a web platform. The system allows administrative personnel authentication through user name and password, display the main menu with relevant options, storage in the database of the company and integration with the trading system terminal company CNEL EP; manages the display of percentages of completion, search for dynamic information, monitoring and reporting crews. This was developed using tools such as the Django framework in version 1.6 for its stability and documentation by allowing an agile and dynamic development with a low cost of production, programming language python, both open source was also used so its integration the database manager PostgreSQL is simple. Therefore the developed software ensures activities in less time, with easy access to information, through a friendly interface and easy to use, improving the quality of information processing, becoming a contribution of technological development for the company.